Public Debt, Productive Public Spending and Endogenous Growth. (31st July 2015) - Greiner, Alfred
<x xml:space="preserve">Abstract</x> We analyse the effects of public debt in a basic endogenous growth model with productive public spending. We demonstrate that a discretionary policy in general violates the intertemporal government budget constraint along a balanced growth path. A balanced government budget gives a unique saddle point stable growth path. With a rule‐based policy, two saddle point stable balanced growth paths can occur, depending on the intertemporal elasticity of substitution of consumption and on the primary surplus policy. Higher debt goes along with smaller long‐run growth and we derive a condition such that a deficit‐financed increase in public spending raises the growth rate.